Introductory chemistry a foundation, annotated instructor's edition - Zumdahl, Steven S.; DeCoste, Donald J. (Cencage Learning, 2015)
Combines problem-solving structure with substantial pedagogy to enable students to become independent problem solvers in the introductory course and beyond. This book captures student interest through coverage of chemical reactions, explanations and visualizations, and an emphasis on everyday applications